«Yo, aquella que sin ley canté algún día». Nuevos hallazgos en torno a la vida y la obra de María de Estrada Medinilla - Andrés Martín, Rubén (El Colegio de México, 2025)
The objective of this study is to present data pertaining to the figure of María de Estrada Medinilla. She is an author who has been well-known for a long while in the world of literary and historical studies; however, almost nothing is known about her private life. This article presents new information about her, demonstrating that she was born in Guatemala into a family with illustrious roots that go back to conquistadores such as Pedro de Estrada, and even to Bernal Díaz del Castillo. It also shows that she played an outstanding role in the literary revolution that led to the introduction of Gongorism in America. Finally, mention is made of several works of hers which have come to light for the first time.